XRD analysis of Cu-Al interconnect intermetallic compound in an annealed micro-chip - Thangaraj, Joseph Sahaya Anand; Chua, Kok Yau; Hng, May Ting; Lee, Cher Chia (2012)
Cu-Al intermetallic compound (IMC) in Cu wire-Al bond pad interconnect interface is drawing attention of researches. However, due to thin IMC thickness, the characterizations of the IMC are limited to expensive and time consuming techniques. An evaluation is performed to use common X-Ray Diffraction (XRD) technique to identify the IMC phase in the crashed Cu wired micro-chip samples. CuAl phase is identified from measurement with lower scanning rate. KOH treatment for enhancing IMC peaks intensity does not work as expected as it etches the IMC as well.